Modeling the Behavior of a MOS Transistor under Fast Neutron and Gamma Irradiation - Petukhov, M. A.; Ryazanov, A. I. (Physics of atomic nuclei, 2019)
A numerical model of trapping of the radiation-induced charge in the bulk and on the surface of the oxide layer of a MOS transistor has been developed. The model takes into account the generation of point defects under fast neutron irradiation. The volume and surface charges obtained by the numerical modeling have been used to calculate the drain—gate characteristic of the MOS transistor exposed to neutron irradiation in different doses and accompanying high-energy gamma-ray irradiation. To model the effect of neutron irradiation, different methods for estimating the rate of point defect generation in a two-component material (SiO 2 ) have been developed. The simulated drain—gate characteristic is shown to agree well with the experimental data obtained at the concentration of hole traps and their capture cross sections lying within the published data for an unirradiated device after exposure to gamma rays from a 60 Co gamma source and after irradiation with fast neutrons with an average energy of ∼1 MeV and accompanying gamma rays using a pool-type reactor.